Non-Invasive Radiation Diagnostic Methods - Utkurxodjayevna, Kattaxodjayeva Dinara; qizi, Qosimboyeva Shodiyabony Baxodir (American Journal of Bioscience and Clinical Integrity, 2025)
This study examines noninvasive radiation diagnostic methods. It shows that film radiography, in which a person receives a radiation dose of 0.5-0.8 mSv, and the more advanced digital method (0.1-0.2 mSv), are less effective. Fluorography, however, focuses on a specific area of the chest and produces images much smaller (approximately 10 x 10 cm). The radiation load on the body ranges from 2 to 10 mSv, equivalent to 2-10 annual doses.